United States National Strategy for Defending Vital Infrastructure from Cyberattacks - Tristantri, Cepi Novia; Prasodjo, Haryo (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The expanding information and communication technology landscape has led to complex security challenges, marked by dynamic and evolving cyber threats including hacking, malware, phishing, data theft, fraud, and Distributed Denial of Service (DDoS). Notably, the United States has faced the highest incidence of cybercrime cases from 2017 to 2021, affecting 2.9 billion victims and resulting in a cumulative material loss of US$18.7 billion during this period. This research centers on the United States, acknowledged as the primary target for global cybercriminals, comprising 38% of cybercrime targets. This research aims to find out the strategic efforts of the United States in overcoming cybercrime that befell its country so that it becomes the best country in cases of alleviating and controlling cases of cyberattacks even though it is also the country with the highest cases of cyberattacks in the world. Utilizing a qualitative research method, the study demonstrates that the United States collaborates systematically and synergistically with state governments, employing a centralized approach to delegate specific tasks and authorities. The study concludes that the United States has implemented the National Cybersecurity Strategy (NCS) 2023 program, aiming to establish a strategic environment and ecosystem by maintaining vital infrastructure and centralized integration.